Taxogenomics Resolves Conflict in the Genus Rhodobacter: A Two and Half Decades Pending Thought to Reclassify the Genus Rhodobacter - Suresh, G.; Lodha, Tushar D.; Indu, B.; Sasikala, Ch.; Ramana, Ch. V. (Frontiers in Microbiology, 2019)
The genus Rhodobacter is taxonomically well studied, and some members are model organisms. However, this genus is comprised of a heterogeneous group of members. 16S rRNA gene-based phylogeny of the genus Rhodobacter indicates a motley assemblage of anoxygenic phototrophic bacteria (genus Rhodobacter) with interspersing members of other genera (chemotrophs) making the genus polyphyletic. Taxogenomics was performed to resolve the taxonomic conflicts of the genus Rhodobacter using twelve type strains. The phylogenomic analysis showed that Rhodobacter spp. can be grouped into four monophyletic clusters with interspersing chemotrophs. Genomic indices (ANI and dDDH) confirmed that all the current species are well defined, except Rhodobacter megalophilus. The average amino acid identity values between the monophyletic clusters of Rhodobacter members, as well as with the chemotrophic genera, are less than 80% whereas the percentage of conserved proteins values were below 70%, which has been observed among several genera related to Rhodobacter. The pan-genome analysis has shown that there are only 1239 core genes shared between the 12 species of the genus Rhodobacter. The polyphasic taxonomic analysis supports the phylogenomic and genomic studies in distinguishing the four Rhodobacter clusters. Each cluster is comprised of one to seven species according to the current Rhodobacter taxonomy. Therefore, to address this taxonomic discrepancy we propose to reclassify the members of the genus Rhodobacter into three new genera, Luteovulum gen. nov., Phaeovulum gen. nov. and Fuscovulum gen. nov., and provide an emended description of the genus Rhodobacter sensu stricto. Also, we propose reclassification of Rhodobacter megalophilus as a sub-species of Rhodobacter sphaeroides.